The Effect of Interactive Video Use on Early Childhood Cognitive Ability - Wahyuni; Rakimahwati (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This study aims to determine the effect of using interactive video on the cognitive abilities of early childhood in Bukittinggi City. The research method used is the Mixed Method with the type of research Sequential Explanatory Design, with the first testing phase using quantitative methods and then deepening with qualitative methods. Data collection techniques for quantitative data using questionnaires and qualitative data with observations and interviews. Quantitative testing was carried out with Pearson's product moment while qualitative data testing was carried out by data triangulation. The results of the coefficient test indicate that between the independent variable and the dependent variable there is a strong and positive and significant relationship between the use of interactive videos on early childhood math skills. The results of qualitative tests from observations and interviews conducted showed that the use of interactive videos was very effective in influencing early childhood math skills. Based on the results of the research above, it can be concluded that there is a positive and significant effect between the use of interactive videos on the math skills of early childhood in Bukittinggi City.